The transcription factor Th-POK negatively regulates Th17 differentiation in Vα14i NKT cells - Engel, Isaac (American Society of Hematology, 2012)
The majority of mouse Vα14 invariant natural killer T (Vα14i NKT) cells produce several cytokines, including IFNγ and IL-4, very rapidly after activation. A subset of these cells, known as NKT17 cells, however, differentiates in the thymus to preferentially produce IL-17. Here, we show that the transcription factor—known as T helper, Poxviruses, and Zinc-finger and Krüppel family, (Th-POK)—represses the formation of NKT17 cells. Vα14i NKT cells from Th-POK–mutant helper deficient (hd/hd) mice have increased transcripts of genes normally expressed by Th17 and NKT17 cells, and even heterozygosity for this mutation leads to dramatically increased numbers of Vα14i NKT cells that are poised to express IL-17, especially in the thymus and lymph nodes. In addition, using gene reporter mice, we demonstrate that NKT17 cells from wild-type mice express lower amounts of Th-POK than the majority population of Vα14i NKT cells. We also show that retroviral transduction of Th-POK represses the expression of the Th17 master regulator RORγT in Vα14i NKT-cell lines. Our data suggest that NKT17-cell differentiation is intrinsically regulated by Th-POK activity, with only low levels of Th-POK permissive for the differentiation of NKT17 cells.